Progressive Cognitive Impairment Evolving to Dementia Parallels Parieto-Occipital and Temporal Enlargement in Idiopathic Chronic Hydrocephalus: A Retrospective Cohort Study - Missori, Paolo; Currà, Antonio (Frontiers in Neurology, 2015)
Little is known regarding progressive enlargement of the ventricular system in symptomatic patients or asymptomatic subjects. Before eventual surgical treatment we evaluated the clinical and radiological features of an extremely rare group of patients with idiopathic chronic hydrocephalus and cognitive impairment evolving to dementia (n=11), and an extremely rare group of asymptomatic or minimally symptomatic adults with ventricular enlargement (n=10). We quantified changes over time in the ventricular frontal, occipital, and temporal horns by measuring the Evans’ index plus a parieto-occipital ratio and a temporal ratio, and their percentage of progression. Cerebral ventricles expanded over very long term in both demented patients with idiopathic chronic hydrocephalus and in asymptomatic or minimally symptomatic adults. In asymptomatic or minimally symptomatic adults, frontal enlargement predominated, whereas demented patients showed predominant parieto-occipital (p=0.00) and temporal (p=0.00) enlargement that progressed faster than in asymptomatic or minimally symptomatic adults (p=0.00). In idiopathic chronic hydrocephalus, progression of cognitive impairment parallels ventricular parieto-occipital and temporal horn enlargement. Limitations of this study are the retrospective nature, the non-uniform use of neuropsychological tests, the reduced sample size due to the extremely stringent enrollment criteria, the inability to determine the precise rate of progression.